IMPROVING GOVERNMENT PUBLIC SERVICES STANDARDS IN INDONESIA: A REVIEW OF THE PUBLIC SERVICE ACT NO. 25/2009 - Evi Oktarina; Evita Isretno Israhadi (Universitas Syiah Kuala, 2023)
Public service has become a critical policy issue due to its limited impact on community transformation. This article explores the range of public services delivered by the Indonesian government under Act Number 25, 2009 on Public Service, as well as the standards and principles governing these services. The research conducted is normative legal research that relies on secondary data to address the issue. Findings reveal that public services can be categorized into two types: services for public goods and services for administration, which are regulated in Article 5 of Act Number 25, 2009 on Public Service. The standards for these services, mandated by the government, can be found in the first paragraph of Article 20 of the same Act. This directive compels the government to provide extensive public services to enhance the well-being of the Indonesian community.